Fracture propagation induced by hydraulic fracturing using microseismic monitoring technology: Field test in CBM wells in Zhengzhuang region, Southern Qinshui Basin, China - Jinbin Zhao; Jinbin Zhao; Peng Liu; Junjun Li; Junjun Li; Zhaoying Chen; Zhaoying Chen; Yang Li; Yang Li; Feng Li (Frontiers in Earth Science, 2023)
Hydraulic fracturing is an important technical measure for coalbed methane (CBM) development, and the propagation of fractures in the target coal seam induced by hydraulic fracturing is related to the stimulation performance in CBM recovery. Therefore, effective monitoring of fracture development during reservoir fracturing is critical for CBM engineering. In this paper, the microseismic technology was used to monitor the spatial and temporal characteristics of the fracture extension in the CBM well during hydraulic fracturing in Zhengzhuang Region, Southern Qinshui Basin, China. Based on the microseismic fracture scanning data and imaging processing, the three-dimensional shape of fractures in vertical wells after fracturing can be quantified, and for the vertical well ZHSY-1, the main fracture direction is identified as NE106°, and the fracture length is 426 m, and the fracture area of coal seam is 1.6 × 105 m2. It is found that fracturing does not develop continuously in time and space with fracturing fluid injection, and the fracture regions are scattered throughout the space, and the formation and development of fracture regions are intermittent. After fracturing with a large amount of fracturing fluid injection in Well ZHSY-1, the fracture area has been significantly increased, and the well gas production has been significantly improved, which is confirmed by the field CBM well data. This study provides a field application case for studying the effect of hydraulic fracturing fracture propagation using microseismic technology, which can be used as a reference for fracturing engineering in CBM development.